Preface to ``Modeling with Measures" - Azmy S. Ackleh; Rinaldo M. Colombo; Sander C. Hille; Adrian Muntean (Mathematical Biosciences and Engineering)
Different communities met in the research workshop ``Modeling withMeasures" that took place at the Lorentz Center (Leiden, TheNetherlands) during 26th--30th of August2013. They were groups of researchers active in the following fields:For more information please click the “Full Text” above.